voorbeeld 6

Rekenregels voor logartimen

Hoofdregel:
$
{}^g\log (x) = y \Leftrightarrow g^y = x
$

Hieruit volgt: $
g^{{}^g\log (x)} = x
$

Daarmee kan je de volgende regels aantonen:

$
\begin{array}{l}
{}^g\log (a) + {}^g\log (b) = {}^g\log (ab) \\
{}^g\log (a) - {}^g\log (b) = {}^g\log (\frac{a}{b}) \\
n \cdot {}^g\log (a) = {}^g\log (a^n ) \\
{}^g\log (a) = \large\frac{{{}\log (a)}}{{{}\log (g)}} \\
\end{array}
$

Voorbeeld 6

$
\begin{array}{l}
\log (K) = 2,8 + 4,9 \cdot \log (L) \\
\log (K) = \log (10^{2,8} ) + \log (L^{4,9} ) \\
\log (K) = \log (10^{2,8} \cdot L^{4,9} ) \\
K = 10^{2,8} \cdot L^{4,9} \\
benaderd: \\
K = {\rm{631}} \cdot L^{4,9} \\
\end{array}
$

©2004-2021 Wiskundeleraar - login